Universality and Selectivity in Income Support: An Assessment of the Issues - Sheila Shaver (Luxembourg Income Study (LIS), 1996)
This paper focuses on four questions: 1) What do universality and selectivity mean in practice in the income support systems of various countries? 2) Are selective income support arrangements more effective than universal ones in ensuring low levels of poverty? 3) Is it true that selective support arrangements concentrate social expenditure on those with least other income, and that in doing so achieve greater redistribution in favor of low income group than universal arrangements? And secondly, do selective income support arrangements achieve a given level of redistribution of income more efficiently than universal ones? and 4) Is it the case that benefit levels are lower under selective than universal income support arrangements?
Keywords: 330